2014
DOI: 10.1002/cae.21605
|View full text |Cite
|
Sign up to set email alerts
|

Online computer supported collaborative learning (CSCL) for engineering students: A case study in Malaysia

Abstract: ABSTRACT:Computer supported collaborative learning (CSCL) via online is an emerging paradigm of educational technology where people can learn together with the help of computer and its related applications. CSCL has become an important and appealing mode of learning across disciplines including engineering. Teamwork is one of the most important elements in engineering profession and collaborative learning is a natural choice for engineering education since it cultivates team among students. This study aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…Online collaborative learning (OCL) environments, such as wikis, blogs, collaborative documents and learning management systems, mediate learning processes, including interaction, discussion, argumentation and reflection (Kirschner, Paas, & Kirschner, ). OCL facilitates learner collaboration and interaction (Goodyear, Banks, Hodgson, & McConnell, ) and provides a flexible CL community (Balakrishnan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Online collaborative learning (OCL) environments, such as wikis, blogs, collaborative documents and learning management systems, mediate learning processes, including interaction, discussion, argumentation and reflection (Kirschner, Paas, & Kirschner, ). OCL facilitates learner collaboration and interaction (Goodyear, Banks, Hodgson, & McConnell, ) and provides a flexible CL community (Balakrishnan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several researches in the literature have investigated students’ attitude and behavior in online learning. Balakrishnan opined that the quality of students’ performance depends very much on computer knowledge, prior experience, and user attitude toward computer related task. Abedin et al found that students’ prior experience with online education affects the adoption level of computer supported collaborative learning environments.…”
Section: Evaluation and Resultsmentioning
confidence: 99%
“…Wang (2016) also indicated that in project learning using Wikis as a tool, learners needed to become more active; learning attitude and participation were particularly important in that case (Balakrishnan, 2015). Characteristics of students and learning strategies taken would affect learning results (Solimeno, Mebane, Tomai, & Francescato, 2008).…”
Section: Online Collaborative Learningmentioning
confidence: 99%
“…Web 2.0 tools have a strong advantage in being able to share information, allowing users to create their own content and communicate with others through various pipelines (Cormode & Krishnamurthy, 2008;Balakrishnan, 2015;Abodoli, Aris, Ahmad, & Rosli, 2015). Some researchers who have attempted to add Web2.0 tools such as Wiki pages, Google Docs and Facebook into learning (Wang, 2016;Abodoli et al, 2015;Hoic, Dlab, & Mornar, 2016)have found that these tools can assist teaching and improve learning outcomes (Alexander, 2006;Boulos, Maramba, & Wheeler, 2006).…”
Section: Introductionmentioning
confidence: 99%